Epidemiological characteristics, management, and outcomes of atrial fibrillation in TUNISIA: Results from the National Tunisian Registry of Atrial Fibrillation (NATURE‐AF). Issue 4 (11th March 2021) - Ouali, Sana; Ben Halima, Afef; Chabrak, Sonia; Chettaoui, Rafik; Ben Halima, Manel; Haggui, Abdeddayem; Krichane, Salma; Noureddine, Larbi; Marrakchi, Sonia; Charfeddine, Selma; Hassine, Majed; Sayahi, Khaled; et al.
Abstract: Background: Contemporary registries on atrial fibrillation (AF) are scare in North African countries. Hypothesis: In the context of the epidemiological transition, prevalence of valvular AF in Tunisia has decreased and the quality of management is still suboptimal. Methods: NATURE‐AF is a prospective Tunisian registry, involving consecutive patients with AF from March 1, 2017 to May 31, 2017, with a one‐year follow‐up period. All the patients with an Electrocardiogram‐documented AF, confirmed in the year prior to enrolment were eligible. The epidemiological characteristics and outcomes were described. Results: A total of 915 patients were included in this study, with a mean age of 64.3 ± 22 years and a male/female sex ratio of 0.93. Valvular AF was identified in 22.4% of the patients. The mean CHA2 DS2 VASC score in nonvalvular AF was 2.4 ± 1.6. Monotherapy with antiplatelet agents was prescribed for 13.8% of the patients. However, 21.7% of the subjects did not receive any antithrombotic agent. Oral anticoagulants were prescribed for half of the patients with a low embolic risk score. In 341 patients, the mean time in therapeutic range was 48.87 ± 28.69%. Amiodarone was the most common antiarrhythmic agent used (52.6%). During a 12‐month follow‐up period, 15 patients (1.64%) had thromboembolism, 53 patients (5.8%) had major hemorrhage, and 52 patients (5.7%) died. Conclusions: NATURE‐AF has provided systematic collection of contemporary data regarding the epidemiological and clinical characteristics as well as the management of AF by cardiologists in Tunisia. Valvular AF is still prevalent and the quality of anticoagulation was suboptimal.